Smart Subsidy Policy: A Digital Governance Framework for Data-Driven Subsidy Management in Indonesia - Nasrul Auwal Affandi Nasrul Affandi; Hayat; Rini Rahayu Kurniati (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2026)
Abstract. Subsidy policies remain essential fiscal instruments for maintaining economic stability, reducing social inequality, and improving public welfare. However, conventional subsidy administration continues to face persistent challenges, including fragmented databases, inaccurate beneficiary targeting, weak institutional coordination, limited data interoperability, and inadequate monitoring mechanisms, resulting in fiscal inefficiency and reduced policy effectiveness. Although previous studies have examined subsidy reform, digital governance, and evidence-based policymaking, these issues have generally been discussed separately, leaving a gap in the development of an integrated governance framework for subsidy management. This study aims to develop a Smart Subsidy Policy framework by integrating digital governance with evidence-based policymaking to strengthen subsidy administration in Indonesia. Using a qualitative approach through a systematic literature review, this research analyzes academic publications, government reports, policy documents, and international institutional reports. The findings indicate that integrating interoperable databases, digital identity systems, artificial intelligence, big data analytics, and real-time monitoring can improve beneficiary targeting, transparency, accountability, fiscal efficiency, and policy responsiveness. The proposed Smart Subsidy Policy framework provides a governance model that integrates technological innovation, institutional coordination, and evidence-based decision-making to enhance subsidy effectiveness and public financial governance, while offering theoretical contributions and recommendations for improving subsidy management and public sector accountability in Indonesia.